(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
China and India contribute to an exceptionally older history and relationship. All through the first millennium, they were the centres of pious and sacred activities. Sacred and edifying interactions survived amid them for the duration of the first few centuries. The Islamic invasion in India made two countries living as aliens until nineteenth century, when Europeans colonized both. Prior to European Colonisation, China and India reported for about 33 percent and 25 percent correspondingly of the world’s manufactured goods. India China trade affairs are the most key ingredient of two-sided relations between India and China.. The India China trade affairs are regulated by the India China JBC, which ensures a free exchange of products and services between the two nations. The major trade indicators used in the study are Import and Export. Another trade indicator used in the study is Commodity Composition. The major economic indicators used in the study are GDP (Real Annual Growth ), GDP per capita, Balance of Trade. Although there are many gaps that define the Indo-China relationship like trade gap (trade deficit between both the Countries), the border perception gap the GDP growth rate gap etc. Instead of the trade gap between both the Countries, among the most encouraging recent developments in India-China ties is the rapid increase in bilateral trade.